Gut Mucosal and Fecal Microbiota Profiling Combined to Intestinal Immune System in Neonates Affected by Intestinal Ischemic Injuries - Romani, Lorenza; Del Chierico, Federica; Chiriaco, Maria; Foligno, Silvia; Reddel, Sofia; Salvatori, Guglielmo; Cifaldi, Cristina; Faraci, Simona; Finocchi, Andrea; Rossi, Paolo; Bagolan, Pietro; D'Argenio, Patrizia; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Early life microbiota plays a crucial role in human health by acting as a barrier from pathogens’ invasion and maintaining the intestinal immune homoeostasis. Altered fecal microbiota (FM) ecology was reported in newborns affected by intestinal ischemia. Our purpose was to describe, in these patients, the FM, the mucosal microbiota (MM) and the mucosal immunity. Fourteen newborns underwent intestinal resection because of extensive and focal intestinal ischemia (EII and FII, respectively). FM and MM were determined through targeted-metagenomics, diversity assignment and Kluskal-Wallis analyses of Operational taxonomic units (OTUs) at phylum and species levels. The mucosal immune cells were analyzed through cytofluorimetry. The FM and MM varied in EII and FII groups, showing in the EII group the predominance of Proteobacteria and Enterobacteriaceae and the reduction of Bacteroidetes and Verrucomicrobia for both microbiota. Particularly, the MM was characterized by a statistically significant reduction of Bacteroides, Lachnospiraceae and Ruminococcaceae and by a higher diversity in the EII compared to FII group. FM showed a prevalence of Proteobacteria, as found in MM, while the Shannon index was lower in the EII compared to FII group. An overall increment in B- and T-lymphocytes and Natural killer (NK) T-like cells was found for EII mucosal samples associated to an increment of TNF-α and INF-γ expressing cells, compared to FII group. FM and MM carry specific signatures of intestinal ischemic lesions. Enterobacteriaceae play a special role in EII and may be crucial in determining and maintaining the grade of inflammation and promoting the ischemia extension.